Các hợp chất methoxyflavonoid và coixol được phân lập từ cây cam thảo đất (Scoparia dulcis Linn) - Liên Hương, Tôn Nữ; Phúc, Bùi Minh; Tú, Huỳnh Diễm; Thùy Trang, Lê Thị (Vietnam Journal of Chemistry, 2016)
Chemical constituents of Scoparia dulcis Linn growing in An Giang province were investigated. The result showed that four compounds, including 5,6,7,8,3’,4’-hexamethoxyflavone (1), 5,7,8,4’-tetramethoxyflavone (2), 5,7-dihydroxy-6,8,3’,4’-tetramethoxyflavone (3) and coixol (4) were isolated from the dichloromethane extract. In which, two methoxyl flavonoid (1) and (2) were firstly isolated from this material. These structures were elucidated by modern spectroscopic methods as ESI-MS, 1D- and 2D-NMR and by comparison to the published data. The study has been continued